PENGARUH ADITIF ION Cu TERHADAP MORFOLOGI KERAK GIPSUM PADA PIPA BERALIRAN LAMINER DENGAN PARAMETER LAJU ALIR - Mangestiono, Wiji (METANA, 2010)
Abstract Parameter in this experimental is flowrate which has some effect on the morfology of cristals produced such as crystal system and crystal size. Study of morfology in this research were needed to justify what kind the crystals is and to know the effects of the adition some aditives. To fullfil this demand analysis of Scaning Electron Microscopy were done and also measurement the mass of crystals. The result of this experiment : the mass of crystals decrease by adition ion Cu2+ five ppm and 10 ppm, but crystal morfology has no difference in its siystem otherwise in its length. Crystal system still orthorhombic. Keywords : crystal, flowrate,morfology, aditive